A camera trap‐based assessment of climate‐driven phenotypic plasticity of seasonal moulting in an endangered carnivore. Issue 2 (19th September 2022) - Laporte‐Devylder, Lucie; Ulvund, Kristine R.; Rød‐Eriksen, Lars; Olsson, Ola; Flagstad, Øystein; Landa, Arild; Eide, Nina E.; Jackson, Craig R.
Abstract: For many species, the ability to rapidly adapt to changes in seasonality is essential for long‐term survival. In the Arctic, seasonal moulting is a key life‐history event that provides year‐round camouflage and thermal protection. However, increased climatic variability of seasonal events can lead to phenological mismatch. In this study, we investigated whether winter‐white (white morph) and winter‐brown (blue morph) Arctic foxes ( Vulpes lagopus ) could adjust their winter‐to‐summer moult to match local environmental conditions. We used camera trap images spanning an eight‐year period to quantify the timing and rate of fur change in a polymorphic subpopulation in south‐central Norway. Seasonal snow cover duration and temperature governed the phenology of the spring moult. We observed a later onset and longer moulting duration with decreasing temperature and longer snow season. Additionally, white foxes moulted earlier than blue in years with shorter periods of snow cover and warmer temperatures. These results suggest that phenotypic plasticity allows Arctic foxes to modulate the timing and rate of their spring moult as snow conditions and temperatures fluctuate. With the Arctic warming at an unprecedented rate, understanding the capacity of polar species to physiologically adapt to a changing environment is urgently needed in order to develop adaptive conservation efforts. Moreover, we provide the first evidence for variations in the moulting phenology of blue and white Arctic foxes. Our study underlines the different intraspecific selective pressures that can exist in populations where several morphs co‐occur, and illustrates the importance of integrating morph‐based differences in future management strategies of such polymorphic species. Abstract : We used camera trap images spanning an eight‐year period to show that phenotypic plasticity allows Arctic foxes to physiologically adapt and modulate the phenology of their moult to match seasonal values of snow duration and temperature in their environment. Moreover, the high temporal resolution of data obtained from the wildlife cameras allowed us to establish for the first time physiological differences between white and blue morph Arctic foxes under warming climatic conditions. The methodology offers great potential to investigate the resilience of endangered species in their natural environment, while minimizing stress and disturbance that could otherwise arise from repeated intensive fieldwork efforts, which was of particular relevance in our study.